Clinical characterization of the Dermatofibrosarcomas at Barretos Cancer Hospital in São Paulo - Fernandes, Larissa de Matos; Vazquez, Vinicius de Lima (Brazilian Journal of Oncology, 2022)
Introduction: Dermatofibrosarcoma (DFSP) is a rare neoplasia from mesenchymal tissues in the skin. It has a high potential for local invasion and a high rate of recurrence after the surgical excision. It appears as a hardened plaque of violaceous color, asymptomatic, which evolves with protuberant nodules. There are few Brazilian studies on DFSP. Therefore, patient's characterization could contribute to future therapeutic studies.Objective: To characterize patients with this cancer and describe their clinical and demographic characteristics; to describe adopted therapeutic, recurrence rate and survival.Methods: Retrospective observational study which analyzes data of the medical record of Barretos Cancer Hospital. The variables were analyzed in terms of the average, median and frequency. The Fisher's exact test and the Chisquare test were used to identify associations among the variables. Analysis of cancer survival with no recurrence were made through confection of Kaplan-Meier curves and the log-rank test.Results: There were 69 patients, 52.2% male and 71% white. The average diagnosis age was 42 years old. Regarding education, elementary school incomplete was 37.7%. The main location of the primary tumor was the trunk (34.8%). Conventional surgery was chosen in all cases of primary tumor and 7.2% underwent adjuvant radiotherapy, of which 36.2% presented local recurrence. Among the patients that had never been treated, the recurrence rate was 9 (24.3%) and the distant recurrence was observed in only one case. The previous treatment, before the hospital treatment, was a variable related to recurrence (p=0.014). Disease-free survival had an average of 23.4 months.Conclusion: Conventional surgery used in all cases obtained, in most cases, stabilization or cure of the disease. The recurrence rate was high, however, it was possible to be controlled. Also, only one patient died because of the disease, confirming the low but deadly potential of the dermatofibrosarcomas.
Keywords: Dermatofibrosarcoma; DFSP; Neoplasia of soft tissues; recurrence; survival; protuberans